Articulating the Suppressed Voices of the Indigenous: Maori Cultural Identity in Patricia Grace's Baby No Eyes (NOBEL: Journal of Literature and Language Teaching, 2023)
This article examines how Patricia Grace’s Baby No Eyes (BNE) amplifies Maori cultural identity. Specifically, this study discusses how the novel places Maori in the center as a way to subvert the colonial and conventional way of writing about the indigenous people. The data is collected from the novel’s narrative structure, points of view, and contents. The analysis focuses on the narrative about the marginalization of Maori by the White people. The novel uses a non-linear narrative that resembles Maori’s story-telling tradition, offering an alternative way of telling stories greatly dominated by modern Western linearity. The novel also employs multiple points of view, representing the egalitarian Maori tradition of giving chances to everybody in telling stories in the community hall. In terms of its contents, BNE foregrounds fundamental issues to the survival of Maori in the land that has been controlled by European descendants. These range from the issue of land rights to the contemporary life of Maori. This article argues that the novel offers a dual approach in articulating the voice of the subaltern: the narrative of resistance in the novel and the invitation for Maori to negotiate their tradition and customs in the changing world.